Pengaruh Kemandirian Belajar Terhadap Kemampuan Komunikasi Matematis Siswa - Indraniati Staimen, Selfina; Napitupulu, Clara; Agustin, Lia (Shofanah Media Berkah, 2024)
Mathematical communication skills are an important aspect in mathematics learning that enable students to articulate their understanding effectively. Learning independence, on the other hand, plays a key role in facilitating students' learning process. In this study, we explored the relationship between learning independence and students' mathematical communication abilities. Quantitative research methods are used by collecting data from middle school students through questionnaires that measure the level of learning independence and mathematical communication tests. Statistical analysis shows that there is a significant positive relationship between the level of learning independence and students' mathematical communication abilities. These results highlight the importance of paying attention to independent learning in an effort to improve students' mathematical communication skills. Pedagogical implications and future research directions are discussed. Based on the results of the research and discussion, it was found that there was a significant positive influence of learning independence on the mathematical communication skills of class VIII students at Fajar Indah High School, West Pademangan, as shown by the contribution value of learning independence to mathematical communication skills of 12.8%.